Survei Karakter Kerjasama pada Atlet Basket di Daerah Istimewa Yogyakarta - Katarina Siena Adyati Prasetyaningtyas; Setyandari Setyandari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to: 1) Know the level of cooperation character of basketball athletes in the Special Region of Yogyakarta; 2) Identify the achievement of cooperation character measurement items that are not optimal. This type of research is descriptive quantitative. The subjects in this study were basketball athletes in the Special Region of Yogyakarta obtained by Convenience Sampling or Accidental Sampling method totaling 80 people. Data collection uses a cooperation character scale with 69 valid items and has an Alpha Cronbach reliability index of 0.95. The data collection technique uses a Likert scale based on aspects: (1) Working together, (2) Conveying positive expectations, (3) Appreciating input, (4) Providing encouragement, (5) Building group spirit.The results showed that most basketball athletes had a very high cooperation character (63%) and high (30%) which indicated they were able to work together. The results of the analysis on the achievement of item scores show that as many as 47 (68%) items of cooperation character in the very high category, 19 (28%) items of cooperation character in the high category and 3 (4%) items in the medium category.